Mediating effect of workplace violence on the relationship between empathy and professional identity among nursing students - Wang, Liping; Li, Haiyang; Chen, Qiongni; Fang, Chunhua; Cao, Lifang; Zhu, Li (Frontiers in Psychology, 2022)
Abstract Background: Studies have reported that empathy had a positive effect on professional identity in nursing students. However, little was known about the mechanism underlying this relationship in nursing students. Objective: The purpose of this study was to investigate the mediating effect of workplace violence between empathy and professional identity. Methods: A total 405 nursing students were investigated using the Chinese Jefferson Scale of Empathy-Health Professional (JSE-HP), the scale of professional identity about nursing students and the workplace violence Incident Survey. Hierarchical regression was used to analyze the mediating effect of workplace violence on the relationship between empathy and professional identity among nursing students. Results: The score of nursing students’ professional identity is 103.69±17.79. Workplace violence had a significant negative correlation with empathy (r=-0.449, P ＜0.001) and professional identity (r=-0.330, P＜0.001). Workplace violence accounts for 14.59% of the total mediating effect on the relationship between empathy and professional identity for nursing students. Conclusions: The level of professional identity of nursing students in this study is low. Workplace violence had a partial significant mediating effect on the relationship between empathy and professional identity. Maybe, it was suggested that nursing students’ professional identity might be improved and driven by decrease workplace violence. Targeted interventions to reduce nursing students’ workplace violence should be developed and implemented. In addition, nursing managers and educators should be aware of the importance of empathy and improve professional identity in nursing students.